THE NEGATIVE EFFECT OF THE WAR ON THE EMPLOYMENT AND INCOME OF UKRAINIANS (INNOVATIVE ECONOMY, 2023)
Samborska O.Yu., Klymchuk O.V. THE NEGATIVE EFFECT OF THE WAR ON THE EMPLOYMENT AND INCOME OF UKRAINIANSPurpose. The aim of the article is to analyse the Ukrainian labour market outlining the most popular vacancies and professions, determining the number of job applicants by region of Ukraine and the size of wages during martial law. Methodology of research. The theoretical and methodological basis of the research is the fundamental provisions of modern economic theory, the scientific works of leading scientists in the field of the labour market. The following methods were used to achieve a set of goals: description for identifying and characterizing approaches to identifying labour market problems in past periods; abstract and logical – for expressing one's own assumptions and forming conclusions; graphic for visual illustration of comparative phenomena.Findings. The negative consequences of military operations on the territory of Ukraine for people of working age are summarized, the number of potential vacancies in the past years and the period of searching for the desired position, which is an average of 6.2 months, are determined. Regions of the country with the largest number of vacancies for in-demand jobs and professions were singled out; the average salary in cities was investigated. It has been established that the largest percentage of dismissals occurs by agreement of the parties. It was determined that in order to overcome the consequences of unemployment, it is worth paying attention to the mechanism of implementing remote work, which is a new challenge of modern realities.Originality. The study of the Ukrainian labor market and negative trends in its condition as a result of military actions on the territory of the country has been further developed, which is manifested in an increase in the time it takes to find a job, mass migration of the working population, and the reluctance of young people to return to Ukraine before the end of martial law.Practical value. Implementation of the proposed practical recommendations for overcoming the negative consequences of military actions for persons of working age can be used in the development of programs for the social and economic development of territories, in strategic plans for the development of enterprises, organizations, and local self-government bodies.Key words: unemployment, vacancies, crisis, demand, workforce.
Keywords: unemployment; vacancies; crisis; demand; workforce.